Spawning in the deep: reproductive life history of four mesopelagic fishes of the northwestern Atlantic Ocean - Lyndsey S. Lefebvre; Heidi M. Sosik; Joel K. Llopiz (Frontiers in Marine Science)
The biomass of mesopelagic fishes is estimated to be on the order of or to exceed that of fishes in the epipelagic. Despite their abundance and importance as an ecological link between surface and deep ocean habitats, there is a dearth of basic life history data for mesopelagic fishes. Reproductive biology data are critical for understanding population dynamics and estimating production of a species, particularly when age and growth data are lacking. Between July 2018 and August 2022, collections were made in the western North Atlantic utilizing multiple net types to capture a broad size-range of mesopelagic fishes. Histological analysis of gonad tissue from four numerically dominant species—Argyropelecus aculeatus (Sternoptychidae), Benthosema glaciale (Myctophidae), Scopelogadus beanii (Melamphaidae), and Sigmops elongatus (Gonostomatidae)—were examined to describe aspects of reproduction. We determined that A. aculeatus and B. glaciale are gonochoristic batch spawners with indeterminate fecundity, and the standard length at which 50% of females were mature (L50) was 39.45 and 33.77 mm, respectively. S. beanii were found to be gonochoristic, iteroparous, and likely have multi-year oocyte development with an L50 of 90.38 mm. S. elongatus was confirmed as a protandrous hermaphrodite, iteroparous, and had an L50 of 200.45 mm. This study is the first to present regional maturity ogives for all four species and to describe detailed reproductive patterns in A. aculeatus, S. beanii, and S. elongatus. These results contribute to the data necessary for quantifying the role of mesopelagic fishes in global biogeochemical cycles and for ensuring responsible use of mesopelagic resources.